(untitled) (Alternautas, 2016)
More than a decade since the eruption of the “progressive cycle” of Latin American governments, a question has become inevitable after the recent presidential elections in Argentina: what is left of the Latin American Left? Is it still possible to isolate divergent tendencies in the Latin American progressive wave at the current moment of generalized international financial domination? Does the question of the ‘exhaustion’ of the progressive cycle not open a gap that invites us to think beyond the popular distinction of the “two Lefts”, proposed by Jorge Castañeda (2006), that strategically separated a “good democratic left” committed to liberalism and the market from an “authoritarian” one, heir to populist and caudillo legacies of the Latin American political tradition?